Utilização de polissacarídeos de algas marinhas na formulação de iogurte light - Freitas, Karla Fernanda da Silva (2023)
The objective of this study was to use agar from the species Gracilaria domingensis and Gracilaria birdea in yogurts, to evaluate the physical-chemical, microbiological and sensorial characteristics. The study evaluated two yogurts with agar from the species under study and the results indicated that there was a significant difference (p<0.05) between the physicochemical variables of the formulas and the absence of Salmonella spp. and thermotolerant coliforms of Staphylococcus aureus. Concluding that the replacement of stabilizers/thickeners of animal origin with natural polysaccharides extracted from seaweed is effective in maintaining the physical-chemical characteristics of yogurt, thus contributing to healthier diets and lifestyles, reaching an audience of vegetarian and vegan consumers.